Pemikiran Islam Soekarno: Dari Klaim Komunis Hingga Rekonsisliasi Negara Kesatuan - Awaluddin Awaluddin (Al-Widad, 2022)
This study discusses the concept of a unitary state within the framework of Islamic ideology from the perspective of Soekarno. The study aims to analyze Soekarno’s thoughts regarding the relationship between Islam, nationalism, and national unity within the context of Indonesia’s pluralistic society. The research employs a library research method with a qualitative-descriptive approach through the analysis of relevant works, speeches, and ideas of Soekarno. The findings indicate that Soekarno viewed Islam as a moral and social value capable of strengthening national unity without necessarily establishing Indonesia as a religious state. According to Soekarno, the concept of a unitary state is built upon the principles of unity, mutual cooperation, and tolerance, which are in harmony with the universal values of Islam. Thus, Soekarno’s thought positions Islam as an ethical force in maintaining the integrity of the Unitary State of the Republic of Indonesia amidst societal diversity.